Improvement of catalytic activity for α‐diimine nickel complex with active sites stabilized by bulky boron counterions at elevated temperature. (9th March 2022) - Wang, Xueer; Feng, Zhongwei; Guo, Wenqi; Zhong, Wentao; Liu, Xiaoyu; Wang, Cheng; Fu, Zhisheng; Fan, Zhiqiang
Abstract : Three α ‐diimine Ni (II) catalysts (Cat.1, Cat.2 and Cat.3 ) were synthesized and investigated for ethylene polymerization using alkyl aluminum and organoboron compounds as binary cocatalyst. The effects of different alkyl aluminum and boron complexes on ethylene polymerization catalyzed by Cat.1, Cat.2, and Cat.3 were studied. The sodium tetrakis[3, 5‐bis (trifluoromethyl)phenyl]borate (NaBArF ) was found to have best promotion for the catalytic activity of Cat.1, compared to negative effect of dimethylanilinium tetrakis (pentafluorophenyl)borate (TTB) and trityl tetrakis (pentafluorophenyl)borate (AB) . All the three catalysts showed higher catalytic activity when NaBArF was introduced into the catalytic system, especially for Cat.3 (increased by 41.3% at 70°C). There was still minor increase of the catalytic activity for Cat.2 which have much better thermostability than Cat.3 . The charging sequence of NaBArF and the [B]/[Ni] ratio have significant effects on the catalytic activity. The better catalytic performance of Cat.1 /AlEt2 Cl/NaBArF could be explained by its ability to raise the number of active centers. Namely, the molar percentage of active centers of Cat.1 /AlEt2 Cl/NaBArF was still above 30%, which was 1.7 times that of Cat.1 /AlEt2 Cl even if polymerization ran up to 30 min based on 2‐thiophenecarbonyl chloride (TPCC) quench‐labeling method. Lower [Al]/[Ni] ratio but more active centers and longer active centers lifetime of this binary cocatalyst is promising for improving the activity of ethylene polymerization industrially at elevated temperature. Abstract : Key findings: We report a novel method to improve the catalytic activity of α ‐diimine nickel catalyst by adding a borate (NaBArF ) into the catalytic system and reveal that the major effect of NaBArF on the catalytic activity is to raise the number of active centers. Lower [Al]/[Ni] ratio but more active centers and longer active centers lifetime of this binary cocatalyst is promising for improving the activity of ethylene polymerization industrially at elevated temperature.